TECHNICAL EDUCATION IN SECONDARY SCHOOLS IN THE ONLINE ENVIRONMENT - DEPESOVA, Jana; KRAJINCAK, Erik (Journal of Technology and Information Education, 2025)
Online education is a characteristic element of modern education in all developed countries of the world. The reality of the present time has brought into education such teaching methods that have not been preferred in high school education until now. Today, this type of education has become part of the educational process in our country, even at elementary or in secondary schools. With such a form of education, it is necessary to realize that this method may not be a guarantee of quality, which stems from the perfect alignment of different methods and from the high-quality processing of didactic material intended for the distance form of education. The aim of the contribution is the comparison of two forms of education, while the online environment will serve as the second teaching tool in the experimental group of pupils. The focus is not only on the curriculum of a theoretical nature, but also on the selection of such topics with a practical content, for which there is a premise of simulation of activities, alternative activity, the possibility of creating a practical activity within the framework of education.
Keywords: online environment; technical education; electrotechnical education; pedagogical experiment